Penerapan Terapi Musik Modern pada Anak Autis Usia TK di Sekolah Bina Anggita Yogyakarta - Adiratna Kusuma, Nurhayati; Zubaedah, Siti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this study was to determine the application of music therapy in kindergartenchildren with autistic age and what is the impact of the application of music therapy inkindergarten children with autistic age. This research was conducted at the Kindergarten School of Bina Anggita Yogyakarta. This research uses descriptive qualitative research methods. The research subjects were therapists, teacher assistants and parents of students, while the object of the study was kindergarten-aged autistic children. Data collection using the method of observation, interviews and documentation. The results showed that: 1) The method used in the application of music therapy for children with autistic age at Kindergarten Bina Anggita Yogyakarta consisted of 3 methods, namely the sampling method, the imitation method, and the habituation method, 2) The impact of the application of music therapy on autistic children kindergarten age at Yogyakarta's Bina Anggita School is impact and has no impact. The impact on Ail's children is seen from the development of concentration, emotional, communication skills, self-confidence, and motor skills. While there is no impact on Vano's children where no development has occurred during the study. This is because the Vano child has a low function autism category so that verbal communication skills and others are less able to develop in short music therapy activities